Urgency of GCIO to Actualize Information Management Based on Connected Government in Yogyakarta Special Region (Urgensi GCIO untuk Mewujudkan Manajemen Informasi Berbasis Connected Government di Daerah Istimewa Yogyakarta) - Agung Harimurti (BBPSDMP KOMINFO MAKASSAR, 2016)
The research is entitled